REMITTING SERONEGATIVE SYMMETRICAL SYNOVITIS WITH PITTING OEDEMA - Neki, N.S.; Jain, Ankur; Bajaj, Rohit; Jindal, Mohit Manav (Journal of Ayub Medical College Abbottabad, 2014)
Remitting seronegative symmetrical synovitis with pitting oedema (RS3PE) is a rare clinical entity often mimicking more common diseases like rheumatoid arthritis (RA) and polymyalgia rheumatica (PMR). Although the exact aetiology is not clear, yet it responds dramatically to low doses of steroids with excellent prognosis unlike RA and PMR. We report a case of 72 year old male agriculturist by profession presenting with acute polyarthritis and pitting oedema of both hands and feet as well as pretibial areas, diagnosed to be a case of RS3 PE. Keywords: Remitting, Seronegative, Synovitis, Elderly